Pentahelix Model Collaboration In Shaping The Independence of Vagrants and Beggars - Ropiah, Eva; Renata, Alma; Wulandari, Sri; Haryo Bharoto, Raden Mahendra (Asian Journal of Social and Humanities, 2024)
This research aims to analyze the collaboration of the pentahelix model in forming the independence of homeless people and beggars. Cirebon City Regional Regulation Number 13 of 2019 concerning the Implementation of Public Order and Community Peace was issued to tackle homeless people and beggars in Cirebon City but its implementation is not yet optimal. The method used in this research is a qualitative method with data collection techniques, interviews, observation and documentation. The theory used is the theory of collaborative governance by (Ansell and Gash, 2008) "Collaborative governance is therefore a type of governance in which public and private actors work together in a distinctive way, using particular processes, to establish laws and rules for the provision of public goods", namely there are five indicators, face-to-face dialogue, building trust, commitment to the process, mutual understanding, and interim results. Based on this research, it can be concluded that the pentahelix model of collaboration in establishing the independence of homeless people and beggars is not optimal, so there is a need for good collaboration and implementing the pentahelix model from each institution to be able to realize the independence of homeless people and beggars in Cirebon City.